Role of CD40 in Prion Disease and the Immune Response to Recombinant PrP - Rubenstein, Richard (2013)
The CD40 receptor-CD40 ligand (CD40-CD40L) interaction has been shown to affect both immune and non-immune cells and is implicated in diverse activities including immunoglobulin class switching (IgM to IgG), atherosclerosis, chronic inflammation and Alzheimer's Disease pathogenesis. A number of groups have studied the role of CD40 in prion disease, however, the results are conflicting presumably due to the use of different scrapie agent-host strain combinations and routes of infection. In the current study, we clarify the effect of CD40 on: (i) replication, progression to clinical disease, PrP(Sc) profile, and neuropathology associated with infection of a single host genotype with three distinct mouse-adapted scrapie strains, and (ii) the immune response of double knockout (PrP, CD40) transgenic mice to recombinant PrP as assessed by the generation of anti-PrP antibodies. Our results suggest that CD40: (i) results in slower disease progression and scrapie strain-specific differences in incubation periods, (ii) does not affect the level of scrapie strain-specific PrP(Sc), (iii) does not influence disease-associated neuropathology, but (iv), as expected, is required to mount an immune response generating anti-PrP IgG antibodies.